2006
DOI: 10.1242/jeb.02087
|View full text |Cite
|
Sign up to set email alerts
|

Contractile recovery from acidosis in toad ventricle is independent of intracellular pH and relies upon Ca2+ influx

Abstract: SUMMARY Hypercapnic acidosis produces a negative inotropic effect on myocardial contractility followed by a partial recovery that occurs in spite of the persistent extracellular acidosis. The underlying mechanisms of this recovery are far from understood, especially in those species in which excitation–contraction coupling differs from that of the mammalian heart. The main goal of the present experiments was to obtain a better understanding of these mechanisms in the toad heart. Hypercapnic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…However, this seems unlikely because myocardial force is known to recover during persistent acidosis with a fairly rapid time course (∼5 min) in both mammals (Orchard 1987) and amphibians (Salas et al 2006). Alternatively, the lack of force recovery during persistent acidosis may be because acid extrusion mechanisms were not activated (or sufficiently activated).…”
Section: Effects Of Hypercapnic Acidosismentioning
confidence: 99%
“…However, this seems unlikely because myocardial force is known to recover during persistent acidosis with a fairly rapid time course (∼5 min) in both mammals (Orchard 1987) and amphibians (Salas et al 2006). Alternatively, the lack of force recovery during persistent acidosis may be because acid extrusion mechanisms were not activated (or sufficiently activated).…”
Section: Effects Of Hypercapnic Acidosismentioning
confidence: 99%
“…However, the concrete mechanisms of Ca 2+ transients are diverse and uncertain. Several studies have shown that the increase of [Ca 2+ ] i is induced by the influx of extracellular Ca 2+ via membrane Ca 2+ channels or Na + /Ca 2+ exchangers34. However, the increase of intracellular Ca 2+ also can be resulted from the mobilization of sarcoplasmic reticulum (SR) during acidosis56.…”
mentioning
confidence: 99%
“…In many studies, an inhibitor of the Na ϩ -K ϩ -ATPase, such as strophanthidin or ouabain, is included in the calibration solution to facilitate the equilibration between extracellular and intracellular [Na ϩ ]. However, many cells died during calibration in the presence of 10 M ouabain as has been used for isolated toad cardiomyocytes (23). We are uncertain whether this was due to Ca 2ϩ overload.…”
Section: Resultsmentioning
confidence: 99%